1965
DOI: 10.1136/jcp.18.3.317
|View full text |Cite
|
Sign up to set email alerts
|

Observations on vitamin B12 in serum and cerebrospinal fluid in multiple sclerosis

Abstract: In both control samples and samples from cases of multiple sclerosis, the B12 concentration in lumbar cerebrospinal fluid was correlated with the concentration in serum. There was no correlation between B12 concentration and total protein in cerebrospinal fluid.A number of estimations of serum B12 were also made with Lactobacillus leichmannii, after extraction in the presence and absence of cyanide. These showed a difference between cases of multiple sclerosis and controls, one interpretation of which might be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

1977
1977
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…B12 levels in the CSF is only 5-10% of the level found in serum (1) . Mean CSF B12 levels on 27 control subjects was 21 .2pg/ml, well in agreement with pre vious reports (8,11,12,19). Although significant correlation was demonstrated between serum and CSF B12 levels in the reports of WORM-PETERSEN (8) and SIMP SON (11) and BASIL et al (12), we avoided observing the correlation between serum and CSF B12 levels in the present study because the microbiological assay is thought to be inadequate to have a good reproducibility at such a low concentration of B 12.…”
Section: Methodssupporting
confidence: 90%
See 2 more Smart Citations
“…B12 levels in the CSF is only 5-10% of the level found in serum (1) . Mean CSF B12 levels on 27 control subjects was 21 .2pg/ml, well in agreement with pre vious reports (8,11,12,19). Although significant correlation was demonstrated between serum and CSF B12 levels in the reports of WORM-PETERSEN (8) and SIMP SON (11) and BASIL et al (12), we avoided observing the correlation between serum and CSF B12 levels in the present study because the microbiological assay is thought to be inadequate to have a good reproducibility at such a low concentration of B 12.…”
Section: Methodssupporting
confidence: 90%
“…There is very little infor mation concerning the transport of B12 from serum to CSF or vice versa . BASIL et al (12) reported high CSF B12 (60-120pg/ml) in B12-treated multiple sclerosis .…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Nevertheless, cobalamin-deficient subjects also had a lower CSF level of the vitamin in comparison to levels measured in non-deficient subjects (67). The correlation between blood and CSF cobalamin contents was not confirmed in some studies (68,69). However, these studies utilized old methods and cobalamin concentrations were at the lowest detectable limit which may imply large impressions.…”
Section: Brain and Csf Cobalaminmentioning
confidence: 92%
“…5 In other studies, the frequency of severe B 12 deficiency is reported to be low. 6,7 Two important enzyme reactions are dependent on adequate vitamin B 12 concentrations in the cell. Malfunction of these enzymes due to vitamin B 12 deficiency leads to high cellular concentrations of methylmalonic acid (MMA) and homocysteine (tHcy), followed by increased concentrations in other biological fluids.…”
Section: Introductionmentioning
confidence: 99%